First Molecular and Phylogenetic Characterization of Equine Herpesvirus-1 (EHV-1) and Equine Herpesvirus-4 (EHV-4) in Morocco - Zineb El Brini; Ann Cullinane; Marie Garvey; Ouafaa Fassi Fihri; Siham Fellahi; Farid Amraoui; Chafiqa Loutfi; Ghizlane Sebbar; Romain Paillot; Mohammed Piro (Animals)
This study aimed to investigate the molecular prevalence and genetic characterization of EHV-1 and EHV-4 in equid populations in Morocco. A total of 154 equids (114 horses, 9 donkeys, and 31 mules) were sampled, with nasal swabs and tissue samples subjected to multiplex real-time PCR for the detection of EHV-1 and EHV-4. Additionally, an isolate from the tissue of an aborted horse fetus was included in the analysis. A subset of EHV-positive samples underwent virus isolation followed by whole-genome sequencing. PCR assays revealed that 42 samples (27%) tested positive for EHV-4, while only 3 samples (1.94%) were positive for EHV-1. Attempts to isolate the virus from EHV-4-positive samples were unsuccessful. However, virus isolation was successful in an EHV-1-positive nasopharyngeal sample from a donkey. Phylogenetic and molecular characterization reclassified the EHV-1 isolated from the donkey as an EHV-8. Meanwhile, the EHV-1 isolated from the aborted fetal tissue was classified as a clade 1 EHV-1 virus. This study is the first to report the molecular prevalence and genetic characterization of EHV-1 and EHV-4 in equid populations in Morocco, providing valuable insights into the distribution and genetic diversity of these viruses in the region.